Autosomal Recessive Spinocerebellar Ataxia 7 (SCAR7) is Caused by Variants in TPP1, The Gene Involved in Classic Late‐Infantile Neuronal Ceroid Lipofuscinosis 2 Disease (CLN2 Disease). Issue 5 (11th March 2013) - Sun, Yu; Almomani, Rowida; Breedveld, Guido J.; Santen, Gijs W.E.; Aten, Emmelien; Lefeber, Dirk J.; Hoff, Jorrit I.; Brusse, Esther; Verheijen, Frans W.; Verdijk, Rob M.; Kriek, Marjolein; Oostra, Ben; et al.
<x xml:space="preserve">Abstract</x> Exome sequencing revealed TPP1 as the causative gene for autosomal recessive spinocerebellar ataxia type 7 (SCAR7). A missense and a splice site variant in TPP1, cosegregating with the disease, were found in two SCAR7 families. TPP1, encoding the tripeptidyl peptidase 1 enzyme, is known as the causative gene for neuronal ceroid lipofuscinosis disease 2 (CLN2). Our findings now expand the phenotypes related to TPP1 variants to SCAR7. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>